2007
DOI: 10.1002/eji.200636417
|View full text |Cite
|
Sign up to set email alerts
|

Increased proliferation of CD8+ T cells in SAP‐deficient mice is associated with impaired activation‐induced cell death

Abstract: Defective signaling lymphocyte activation molecule (SLAM)-associated protein (SAP) is responsible for the human X-linked lymphoproliferative syndrome. Defects in T helper 2, natural killer, natural killer T and B cells have been demonstrated in SAP-deficient humans and mice, and increased proliferation of CD8 + T cells has been observed. In the current study, we investigated the properties of CD8 + T cell proliferation and activation-induced cell death (AICD), using OT-I T cell receptor (TCR)-transgenic mice o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 58 publications
(90 reference statements)
6
31
0
Order By: Relevance
“…These can cause immunopathology if they are recruited into antiviral responses and fail to contract postinfection. In addition to T cell anergy, activation-induced cell death and the proapoptotic molecule Bim keep autoreactive CD8 + T cells in check (19)(20)(21). Extrinsic mechanisms also operate to repress self-reactive T cells; these include availability of cytokines, such as IL-7 and IL-15 (22,23), and the suppressive effect of regulatory T cells through their ability to secrete IL-10 and TGF-b (24).…”
Section: Cd8 + T Cells Responding To Viral Infections Initiate Their mentioning
confidence: 99%
“…These can cause immunopathology if they are recruited into antiviral responses and fail to contract postinfection. In addition to T cell anergy, activation-induced cell death and the proapoptotic molecule Bim keep autoreactive CD8 + T cells in check (19)(20)(21). Extrinsic mechanisms also operate to repress self-reactive T cells; these include availability of cytokines, such as IL-7 and IL-15 (22,23), and the suppressive effect of regulatory T cells through their ability to secrete IL-10 and TGF-b (24).…”
Section: Cd8 + T Cells Responding To Viral Infections Initiate Their mentioning
confidence: 99%
“…Chen et al recently observed a survival advantage for SAP-knockout murine CD8 + T cells 48 hours after primary stimulation, which they characterized as a defect in activation-induced cell death (AICD) (21). As Strasser and colleagues recently pointed out, the term "AICD" is broadly used to refer to any form of lymphocyte death after antigen stimulation and does not distinguish between the possible mechanisms of lymphocyte apoptosis described above (22).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, p73 deficiency was detected in SAP negative mouse T cells and this was connected with impairment of activation induced cell death. 42 The postulated scenario is shown in Figure 2: SAP expressed at high levels in the late phases of T cell activation binds VCP. In this state the VCP activity may be impaired and therefore it does not elevate NFκB activity.…”
Section: Discussionmentioning
confidence: 99%